Cryptosporidium baileyi in wild captive psittacines in Brazil - Oliveira, Bruno César Miranda [UNESP]; Nagata, Walter Bertequini [UNESP]; Arana, David Giraldo [UNESP]; Ferreira, Gabriela Cortellini [UNESP]; Sitton, Heliton Aparecido [UNESP]; de Oliveira, Marcelo Rodrigues Freitas; Meireles, Marcelo Vasconcelos [UNESP] (Elsevier, 2017)
Cryptosporidiosis in birds manifests as an acute or chronic disease of the respiratory or digestive tracts. The objective of our study was to perform the molecular characterization of Cryptosporidium spp. in wild psittacines kept in captivity at the Araçatuba Municipal Zoo, São Paulo, Brazil. A total of 47 fecal samples were collected from Amazona aestiva, Psittacara leucophthalma, and Ara ararauna. All samples were collected at the time the birds defecated. DNA extraction was performed using the ZR Fecal DNA MiniPrep™ kit (Zymo Research). Screening for Cryptosporidium spp. was accomplished using nested PCR targeting the 18S RNA gene and sequencing of amplified fragments. Positivity for Cryptosporidium spp. (10.64%; 5/47) was found in A. ararauna (4) and P. leucophthalma (1) samples. The amplified fragments were sequenced and showed 100% genetic similarity with Cryptosporidium baileyi.
Keywords: Cryptosporidiosis; Cryptosporidium baileyi; Nested PCR; Psittaciformes